Natural ingredients in the regulation of abnormal lipid peroxidation: a potential therapy for pulmonary diseases - Yundou Liu; Chunyi Wang; Mengru Li; Yi Zhu; Ke Liu; Yufei Liu; Maocai Luo; Chuantao Zhang (Frontiers in Pharmacology)
Pulmonary diseases are a major category of diseases that pose a threat to human health. The most common drugs currently used to treat lung diseases are still chemical drugs, but this may lead to drug resistance and damage to healthy organs in the body. Therefore, developing new drugs is an urgent task. Lipid peroxidation is caused by the disruption of redox homeostasis, accumulation of reactive oxygen species (ROS), depletion of glutathione (GSH), and inactivation of glutathione peroxidase 4 (GPX4). Lipid peroxidation is closely related to the occurrence and progression of respiratory diseases, including acute lung injury, asthma, pulmonary fibrosis, pulmonary hypertension, chronic obstructive pulmonary disease, and lung cancer. Natural ingredients have high safety, high availability, and low cost, and can regulate lipid peroxidation through multiple pathways and targets, making them valuable new drugs. This article aims to summarize the pharmacology and mechanism of natural ingredients targeting lipid peroxidation in the treatment of lung diseases. The reviewed data indicate that natural ingredients are a promising anti-lipid peroxidation drug, mainly alleviating lipid peroxidation through the cystine/glutamate antiporter (System Xc−)/GSH/GPX4 axis, Nrf2 pathway, and ROS pathway. In the future, it will still be necessary to further study the mechanisms of natural products in treating pulmonary diseases through lipid peroxidation and conduct multi-center, large-sample clinical trials to promote the development of new drugs.